Sport psychology services provided to the Brazilian athletes at the Guadalajara 2011 Pan American Games and the London 2012 Olympic Games - Pineschi, P.; Viveiros, L. (Revista Iberoamericana de Psicologia del Ejercicio y el Deporte, 2018)
The Brazilian Olympic Committee (BOC) provided sport psychology services to the athletes and national teams during the 2011 Pan American Games and the 2012 Olympic Games. The first author of this article was part of the Brazilian delegation as an associate member of the BOC Sports Science Department and responsible for the provision of these services. Despite the large amount of literature on the Olympic experience of athletes and on best practices regarding on-site psychological services, few studies have detailed the number and types of interventions that a sport psychologist carries out at the Olympic Games. The objective of this article, therefore, is to present an example of the work of a psychologist in the context of major sporting events, which, in this case, is the work carried out by the first author at the 2011 Pan American Games and the 2012 Olympic Games, exploring the nature and the frequency of each type of intervention employed: (a) psychological evaluations; (b) mental training; (c) counseling; (d) group meetings with athletes; (e) meetings with coaches and team leaders. The number of people who had access to the psychology services was 19 athletes from 5 sports, and 13 of them also were followed up by the psychologist during their training and/or competitions. There was a grand total of: 58 individual consultations, 5 group meetings with athletes and 10 formal meetings with coaches and team leaders. These interventions were well received by both athletes and coaches.